A STUDY ON MARKETING PROBLEMS OF COTTON GROWERS IN PERAMBALUR DISTRICT - et al., R.RAMADOSS (International Journal of Advanced Science and Technology, 2019)
Cotton cultivation wants to be sustainable, offer living precautions to millions of marginal and small farmers; such an enterprise has to be knowledge-based and market–driven and needs to evolve continuously through innovations in front line sciences to break yield and quality difficulty for pleasing present and future national needs and attaining international competitiveness with larger spin–off benefits to India. The purpose of the study was to find out the extent of marketing problems faced by the growers in cotton cultivation and to explore the associations of the farmers' selected characteristics with their marketing problems faced in cotton cultivation. To find out the marketing problems of the cotton growers to offer valued suggestions with regards of marketing problems in Perambalur district. The present study statistical tools used were as percentage analysis, chi-square analysis, nova analysis and ranking analysis. Whereas regulated market and co-operative marketing societies do not the supply facilities. This problems leads to loss of arrivals of cotton sale of the same in co-operative marketing societies and regulated market.